Análisis de la competitividad del sector petrolero mexicano dentro de la integración energética en Norteamérica, 1990-2006 - Camarena Zaragoza, Oliver (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The present investigation has like principal objective, to determine that the exterior petroleum politics of the country, as well as the competitiveness of the national petroleum sector, were two determinant factors in the energy integration with the United States and Canada. The analysis period sets off from 1990 to 2006; period during which there begins to be realized the study of the competitiveness of the petroleum sector of Mexico, across the index of the Revealed Comparative advantage (VCR). For the calculation of this index there were used information of the imports and entire exports of the country, as well as of the imports and exports of oil. The use of this index allowed determining the competitiveness of the sector, which is located at the same countries level like the United Kingdom, Canada, and the United States, between others. Also, it was possible to obtain the level of specialization of Mexico in the oil production. For the case of the petroleum politics, it begins with a historical analysis of what has been the evolution of Mexico like exporting country of oil. As complement, there appeared three different prognoses of the apparent consumption of oil of Mexico, the United States and Canada, like fundamental elements to determine the future demand. The energy integration of the region was tackled by an analysis of that it has been, until now, the commerce of energy between three countries. Of equal way, an analysis was done with information of the volume of production of oil and the percentage of this one in the exports inside the region. Like complement, an analysis was done on the convergence of the oil prices of the whole region of North America, using tests of unitary root of Dickey and Fuller (1979) and Perron (1997) that allows the structural change. All this, threw conclusive information about the integration of the markets of the oil in the region of North America.

La presente investigación tiene como objetivo principal, determinar que la política petrolera exterior del país, así como la competitividad del sector petrolero nacional, fueron dos factores determinantes en la integración energética con Estados Unidos y Canadá. El período de análisis parte de 1990 hasta el 2006; período durante el cual comienza a realizarse el estudio de la competitividad del sector petrolero de México, a través del índice de la Ventaja Comparativa Revelada (VCR). Para el cálculo de este índice se emplearon datos de las importaciones y exportaciones totales del país, así como de las importaciones y exportaciones de petróleo. El uso de este índice permitió determinar la competitividad del sector, la cual se ubica al mismo nivel de países como Reino Unido, Canadá, Estados Unidos, entre otros. También, se pudo obtener el nivel de especialización de México en la producción de petróleo. Para el caso de la política petrolera, se partió de un análisis histórico de lo que ha sido la evolución de México como país exportador de petróleo. Como complemento, se presentaron tres distintos pronósticos del consumo aparente de petróleo de México, Estados Unidos y Canadá, como elementos fundamentales para determinar la demanda futura. La integración energética de la región se abordó con un análisis de los que ha sido, hasta el momento, el comercio de energéticos entre los tres países. De igual manera, se hizo un análisis con datos del volumen de producción de petróleo y el porcentaje de ésta en las exportaciones dentro de la región. A manera de complemento, se hizo un análisis sobre la convergencia de los precios del petróleo de toda la región de Norteamérica, empleando pruebas de raíz unitaria de Dickey y Fuller (1979) y Perron (1997) que permite el cambio estructural. Todo ello arrojó información concluyente sobre la integración de los mercados del petróleo en la región de Norteamérica.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2009-0002; PEMEX; Ventaja comparativa; América del Norte; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/924